DOWNWELLING DIFFUSE ATTENUATION COEFFICIENTS FROM IN SITU MEASUREMENTS OF DIFFERENT WATER TYPES - Bisman Nababan; Veronica S.A. Louhenapessy; Risti E Arhatin (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2013)
Process of light reduction or loss (attenuation) by scattering and absorption is affected bysolar zenith, time, depth, and seawater constituents. Downwelling diffuse attenuation coefficient (Kd)is important to understand for light penetration and biological processes in ocean ecosystem. It is,therefore, important to know the Kd value and its variability in ocean ecosystem. The objective of thisstudy was to determine downwelling diffuse attenuation coefficients and its variability form in situmeasurements of different water types. In situ downwelling irradiances (Ed) were measured using asubmersible marine environmental radiometer instrument (MER) during a clear sky, calm watercondition, and at the time range of 10:30 a.m. up to 14:00 p.m. local time in the northeastern Gulf ofMexico in April 2000. In general, Ed values decreases exponentially with depth. Ed at 380 nmexhibited the lowest attenuation (the most penetrative light), while Ed at 683 nm exhibited the highestattenuation (the most light loss at the top of water column). Overall, the Kd patterns tended to decreasefrom 380 nm to 490 nm (blue-green wavelength), and increase from 490 nm to 683 nm (green-redwavelength). Kd values in offshore region were relatively lower than in coastal region. Kd can be usedto determine the depth of euphotic zone in offshore or teh case-1 water type and the depth of oneoptical depth (the water column depth where the ocean color satellite can possibly sense).